Enhanced Immunomodulatory Effect of Intravenous Immunoglobulin by Fc Galactosylation and Nonfucosylation - Mimura, Yusuke; Mimura-Kimura, Yuka; Saldova, Radka; Rudd, Pauline M.; Jefferis, Roy (Frontiers in Immunology, 2022)
Intravenous immunoglobulin (IVIG) is used as an immunomodulatory agent in the treatment of various autoimmune/inflammatory diseases although its mechanism of action remains elusive. Recently, nonfucosylated IgG was shown to be preferentially bound to Fcγ receptor IIIa (FcγRIIIa) on circulating natural killer cells; therefore, we hypothesized that nonfucosylated IVIG may modulate immune responses through FcγRIIIa blockade. Here, homogeneous fucosylated or nonfucosylated glycoforms of normal polyclonal IgG bearing sialylated, galactosylated or nongalactosylated Fc oligosaccharides were generated by chemoenzymatic glycoengineering to investigate whether the IgG glycoforms can inhibit antibody-dependent cellular cytotoxicity (ADCC).　Among the six IgG glycoforms, galactosylated, nonfucosylated IgG (G2)2 having the highest affinity to FcγRIIIa inhibited ADCC most potently. In mice with collagen antibody-induced arthritis, the (G2)2 glycoform of IVIG had stronger anti-inflammatory activity at a low dose (0.1 g/kg) than the 10-fold higher dose of native IVIG. These results demonstrate that the anti-inflammatory activity of IVIG is in part mediated via activating FcγR blockade by galactosylated, nonfucosylated IgG, suggesting that such nonfucosylated IgG glycoforms in serum and bound to FcγRs on immune cells play immunomodulatory roles in health and disease. This study provides insights into therapeutic strategies for autoimmune/inflammatory diseases and clinical application of glycoengineered recombinant Fc as an alternative to plasma-derived IVIG.